Dynamics of Advocacy for Relocating Fishermen’s Residences in Tambakrejo Village, Semarang City - Kismartini, Kismartini; Widowati, Nina; Warsono, Hardi (KnE Social Sciences, 2022)
The relocation of fishermen’s residences from the banks of the East Banjir Kanal river in Semarang City to new residential locations has resulted in a prolonged conflict between the local Government and the fishing community. Through a coalition of advocacy from various actors, the relocation was finally successfully implemented and accepted by all parties, although it took three years. This study aimed to describe and analyze the community’s reaction and the impact of the advocacy coalition on the policy of relocating fishermen’s residences in Tambakrejo Village. Phenomenological qualitative research methods were used, combined with a quantitative descriptive approach. The findings revealed that the community was initially hostile to the Government’s plan to relocate residents, with the main reason being that it was too far away from the sea, where they earned a living. The advocacy coalition led to the provision of new residential buildings for the fishermen and increased community satisfaction with the new housing. Keywords: policy advocacy, policy dynamics, relocation, community reaction, outcome of advocacy